2021
DOI: 10.3390/microorganisms9071466
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum TWK10 Improves Muscle Mass and Functional Performance in Frail Older Adults: A Randomized, Double-Blind Clinical Trial

Abstract: Sarcopenia is a condition in which there is a loss of muscle caused by aging and it is one of the most significant factors that affects physical fragility. In recent years, the role of the gut–muscle axis has garnered attention as, along with the gut microbiota, it potentially plays a significant role in muscle regeneration, in addition to nutritional supplements and exercise training. Past studies have found that supplementation with Lactobacillus plantarum TWK10 could effectively increase the muscle mass of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 43 publications
0
43
0
Order By: Relevance
“…There is even less research examining how probiotic supplementation impacts muscle mass and function in elderly humans. The single study performed to date found that Lactobacillus plantarum TWK10 had beneficial effects on muscle mass and strength in frail elderly people ( 74 ). Our study has confirmed that microbiota-based treatments could help limit sarcopenia in this population.…”
Section: Discussionmentioning
confidence: 99%
“…There is even less research examining how probiotic supplementation impacts muscle mass and function in elderly humans. The single study performed to date found that Lactobacillus plantarum TWK10 had beneficial effects on muscle mass and strength in frail elderly people ( 74 ). Our study has confirmed that microbiota-based treatments could help limit sarcopenia in this population.…”
Section: Discussionmentioning
confidence: 99%
“…60 Twenty-two studies were double-blind RCTs, [37][38][39][40][41][42][43][44][45][46][47][49][50][51][52][53][54][55][56][57][58]60 of which one was crossover double-blind RCT, 37 one was a single-blind RCT 48 and one was nonblinded. 59 Twelve studies provided probiotics in adults aged 50 years and above, 38,41,43,[47][48][49][50]54,[57][58][59][60] whereas 12 studies in adults below 50 years of age. 37,39,40,42,[44][45][46][51][52][53]55,56 Eight studies were conducted in adults with o...…”
Section: Resultsmentioning
confidence: 99%
“…59 Twelve studies provided probiotics in adults aged 50 years and above, 38,41,43,[47][48][49][50]54,[57][58][59][60] whereas 12 studies in adults below 50 years of age. 37,39,40,42,[44][45][46][51][52][53]55,56 Eight studies were conducted in adults with overweight and/or obesity, [42][43][44][45][46]49,50,56 seven in untrained and non-athletic healthy populations, 37,40,41,51,54,55,59 one in resistance-trained individuals, 53 one in individuals with metabolic syndrome and type 2 diabetes 48 or hypertension, 60 one in people with frailty, 38 one in people with low bone mineral density, 58 one in patients with chronic heart failure, 57 one in participants with non-displaced distal radius fracture, 47…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that the administration of Lactiplantibacillus plantarum TWK10 (TWK10) exerted beneficial effects on improving exercise performance, increasing muscle mass and strength in both mice and humans, and attenuating ageassociated cognitive decline and loss of bone mass in mice. We further found that long-term TWK10 administration did not result in significant histological changes in the organs of mice or alterations in hematological and biochemical parameters in humans [19][20][21][22]. In this study, we comprehensively assessed the safety of TWK10 as a probiotic for human consumption using both in vitro and in vivo approaches.…”
Section: Introductionmentioning
confidence: 94%